Anticancer properties and chemical investigation of seeds and fruits of Phaleria Macrocarpa (SCHEFF.) boerl / Ma Ma Lay - Ma, Ma Lay (2014)

(untitled)
Traditional herbal medicine has been widely used in the treatment of various diseases. A number of herbal medicines have been shown to have a favourable effect in treating cancer or cancer-related diseases. Phaleria macrocarpa (Scheff.) Boerl is one of the traditional herbal medicines that appear to be useful for treating patients who are hypertensive, diabetic and cancerous. This affect may be associated to its high antioxidant, antimicrobial, anti-inflammatory, and cytotoxic activities as well as other bioactivities present in its chemical constituents. The present study employed a bioassay - guided fractionation and purification of bioactive compounds from the P. macrocarpa plant. The methanol extract and fractions of the fruits and seeds of the plant were first screened for their cytotoxic potential using MTT cell proliferation assay. Chemical investigation of the bioactive ethyl acetate then led to the isolation and identification of several chemical constituents. Fractionation of the ethyl acetate fraction of P. macrocarpa seeds yielded palmitic acid, beta-sitosterol and (Z)-9, 17-octadecadienal. The ethyl acetate fraction of P. macrocarpa fruits yielded β-sitosterol, a mixture containing stigmast-4-en-3-one, 2, 4', 6-trihydroxy-4-methoxybenzophenone, and 1-(2, 6-dihydroxy-4-methoxyphenyl)-2-(4-hydroxyphenyl) ethanone. The compounds 2, 4', 6-Trihydroxy-4-methoxybenzophenone, 1-(2, 6-dihydroxy-4-methoxyphenyl)-2-(4-hydroxyphenyl) ethanone and 9, 17-octadecadienal were tested for cytotoxicity on the human colon carcinoma HT-29 cell line and normal human fibroblast lung MRC-5 cell line using the MTT assay. These compounds displayed cytotoxic effect on the HT-29 cell line in a dose- and time-dependent manner but exhibited very low cytotoxic effect on the normal MRC-5 cell line. Morphological features of apoptosis such as cell shrinkage, membrane blebbing, nuclear condensation iv and DNA fragmentation under inverted, phase and fluorescence microscopy were then examined. The effects of the compounds on cells were further analysed using the Annexin V-FITC/PI assay. In this assay, the percentage of early apoptotic, late apoptotic, necrotic and live cells were determined and it was observed that cell death was induced in a dose- and time-dependent manner in HT-29 cells. Results of cell cycle analysis further confirmed that G0/G1 arrest and S-phase accumulation of HT-29 cells declined in a time-dependent manner after treatment with the compounds. Taken together, these results suggested that the induced cell death resulting from treatment with the compounds were possibly associated with changes in the protein expression. The cell death also showed many characteristic of an apoptotic form of cell death. Thus, these compounds merit further investigation as potential anticancer agents.